Compound heterozygotes for filaggrin gene mutations do not always show severe atopic dermatitis. (13th August 2016) - Sekiya, A.; Kono, M.; Tsujiuchi, H.; Kobayashi, T.; Nomura, T.; Kitakawa, M.; Suzuki, N.; Yamanaka, K.; Sueki, H.; McLean, W.H.I.; Shimizu, H.; Akiyama, M.
Abstract: Background: Mutations in FLG, which encodes profilaggrin, cause ichthyosis vulgaris (IV) and are an important predisposing factor for atopic dermatitis (AD). IV shows autosomal hemidominant (semidominant) inheritance, and patients with bi‐allelic FLG mutations tend to have severe IV phenotypes. However, the effect of bi‐allelic FLG mutations on AD incidence and severity remains a subject of controversy. Objective: In this study, we studied individuals with bi‐allelic null FLG mutations to elucidate the effect of bi‐allelic FLG mutations on AD incidence and severity. Methods: Six individuals with bi‐allelic FLG null mutations from three families of IV/AD were investigated. We report the detailed clinical features of the individuals. The phenotype was confirmed by the clinical examinations and the severity of IV and AD was scored using ichthyosis score and Eczema Area and Severity Index (EASI). Result: It was found that five of the six patients had severe IV, and the remaining patient showed moderate IV. Two of the six had moderate AD and three of the six had mild AD. The remaining patient had no AD. Conclusion: Our results suggest that individuals with bi‐allelic FLG mutations do not always have severe AD and confirm that not all individuals with bi‐allelic FLG mutations have AD.